Rapid 5′ Nuclease (TaqMan) Assay for Detection of Virulent Strains of Yersinia enterocolitica - Vishnubhatla, A. (American Society for Microbiology, 2000)
We have developed a rapid procedure for the detection of virulent Yersinia enterocolitica in ground pork by combining a previously described PCR with fluorescent dye technologies. The detection method, known as the fluorogenic 5′ nuclease assay (TaqMan), produces results by measuring the fluorescence produced during PCR amplification, requiring no post-PCR processing. The specificity of the chromosomal yst gene-based assay was tested with 28 bacterial isolates that included 7 pathogenic and 7 nonpathogenic serotypes of Y. enterocolitica, other species of Yersinia (Y. aldovae, Y. pseudotuberculosis, Y. mollaretti, Y. intermedia, Y. bercovieri, Y. ruckeri, Y. frederiksenii, and Y. kristensenii), and other enteric bacteria (Escherichia, Salmonella, Citrobacter, and Flavobacterium). The assay was 100% specific in identifying the pathogenic strains of Y. enterocolitica. The sensitivity of the assay was found to be ≥10(2) CFU/ml in pure cultures and ≥10(3) CFU/g in spiked ground pork samples. Results of the assay with food enrichments prespiked with Y. enterocolitica serotypes O:3 and O:9 were comparable to standard culture results. Of the 100 field samples (ground pork) tested, 35 were positive for virulent Y. enterocolitica with both 5′ nuclease assay and conventional virulence tests. After overnight enrichment the entire assay, including DNA extraction, amplification, and detection, could be completed within 5 h.